LITERACY COLLABORATION: INCREASING THE COMPETENCE OF TEACHERS AND JUNIOR HIGH SCHOOL STUDENTS IN BUILDING A LITERACY CULTURE AT SMP N 23 MEDAN - Tengku Ratna Soraya; Hesti Fibriasari; Wahyu Tri Atmojo; Trisnawati Hutagalung; Oksari Anastasya Sihaloho; Rita Suswati (Prodi Sastra Inggris UKI, 2025)
To enhance students' abilities and knowledge at SMP N 23 Medan, optimizing school literacy culture is crucial. Integrating literacy into the curriculum through activities like reading, essay writing, and discussions can be a starting point. Engaging and enjoyable literacy activities can boost students' learning motivation and skills. Capacity building for both teachers and students through effective training and workshops is also essential. Collaboration between the school, parents, and the community is key to fostering literacy awareness and creating a supportive environment for developing reading, writing, and critical thinking skills. Literacy collaboration activities at SMP N 23 Medan have already yielded positive outcomes, with teachers becoming more adept at literacy strategies and students showing improved skills, exemplified by a student's storytelling performance of